Exercise to reduce the escalation of cocaine self-administration in adolescent and adult rats - Zlebnik, Natalie E. (2012)
RATIONALE: Concurrent access to an exercise wheel decreases cocaine self-administration under short access (5 h/day for 5 days) conditions and suppresses cocaine-primed reinstatement in adult rats. OBJECTIVE: The effect of exercise (wheel running) on the escalation of cocaine intake during long access (LgA, 6 h/day for 26 days) conditions was evaluated. METHODS: Adolescent and adult female rats acquired wheel running, and behavior was allowed to stabilize for 3 days. They were then implanted with an iv catheter and allowed to self-administer cocaine (0.4 mg/kg, iv) during 6-h daily sessions for 16 days with concurrent access to either an unlocked or a locked running wheel. Subsequently, for ten additional sessions, wheel access conditions during cocaine self-administration sessions were reversed (i.e., locked wheels became unlocked and vice versa). RESULTS: In the adolescents, concurrent access to the unlocked exercise wheel decreased responding for cocaine and attenuated escalation of cocaine intake irrespective of whether the locked or unlocked condition came first. However, cocaine intake increased when the wheel was subsequently locked for the adolescents that had initial access to an unlocked wheel. Concurrent wheel access either before or after the locked wheel access did not reduce cocaine intake in adults. CONCLUSIONS: Wheel running reduced cocaine intake during LgA conditions in adolescent but not adult rats, and concurrent access to the running wheel was necessary. These results suggest that exercise prevents cocaine seeking and that this effect is more pronounced in adolescents than adults.